The impact of a social norms approach on reducing levels of misperceptions around smokefree hospital entrances amongst patients, staff, and visitors of a NHS hospital: a repeated cross-sectional survey study - Scott Crosby; Diane Bell; Gerard Savva; Becky Edlin; Bridgette M. Bewick (BMC, 2018)
Abstract Background Smoking is a cause of avoidable morbidity and mortality. In the United Kingdom (UK) the national smoking ban inside hospital buildings is widely adhered to. There is a perception it has led to smokers congregating around hospital entrances (Selbie D. 2016, It's time for a truly smokefree NHS. Public Health Matters Blog. Public Health England). Efforts to shift social norms and create positive smokefree environments might be strengthened by delivering social norms messages. This study explored the impact of a social norms approach campaign to reduce levels of misperceptions surrounding support for smokefree hospital entrances. Method Repeated cross sectional study design. Staff, patients, and hospital visitors at Pinderfields National Health Service (NHS) Hospital (Wakefield, United Kingdom (UK)) completed a survey before and after implementation of a public health social norms campaign (n = 481 surveyed before; n = 459 surveyed after). The main outcome measure was difference between perceived and reported levels of support for smokefree hospital entrances. Results There were high levels of support for smokefree hospital entrances. The majority of participants agreed that patients (n = 849, 90% agreed), staff (n = 863, 92% agreed), and visitors (n = 850, 90% agreed) should not smoke in the hospital entrance. Participants underestimated the proportion of others who self-reported keeping the entrance smokefree. Over 90% of respondents reported not smoking in the hospital entrance, but the perception was that between 50 to 75% of hospital staff, patients, and visitors did not smoke in the hospital entrance. The mean percentage of hospital staff, patients, and visitors who respondents thought did not smoke in entrances was higher for respondents responding after, compared to those responding before, the campaign. There was an overall significant effect of time on attitudes towards smoking in the entrances; in all instances the mean percentage of hospital staff, patients, and visitors the participants believed agreed that hospital entrances should be smokefree was higher for those responding after, compared with before, the campaign. Conclusions People hold misperceptions of the proportion of people who choose to smoke in the hospital entrance. The social norms approach campaign was associated with a strengthening of positive social norms. Such campaigns should be considered by Trusts as one evidence-based based tactic to denormalise smoking, increase support for smokefree policies.